Satisfacción del usuario y calidad del cuidado de enfermería en el servicio de medicina Hospital Leoncio Prado Huamachuco - Escobedo Alayo, Maruja Milda (2019)
The present research, quantitative and descriptive in nature, had as main objective to determine the relationship between the level of satisfaction of the hospitalized user and the quality of nursing care in the medicine service of the Leoncio Prado Huamachuco Hospital, 2019. The sample was constituted by 41 adults hospitalized in the medical service of the Leoncio Prado Huamachuco hospital who met the inclusion criteria. To collect the information, a Likert scale was used, consisting of 24 items to assess the quality of nursing care and another to measure user satisfaction, which consists of 7 simple questions. The research resulted in 29.3% of hospitalized adults who have a good level of satisfaction and perceive a quality level of regular nursing care.